PENGGUNAAN ANTIBIOTIK YANG AMAN DAN RASIONAL PADA PENGOBATAN PENYAKIT INFEKSI DI BIDANG KEDOKTERAN GIGI - Sunarso Brotosoetarno (Faculty of Dentistry, Universitas Indonesia, 2015)
The use of antibiotics on infections in dentistry has been known for year recently, a lot of dentists entertained the failures of using antibiotics. There are several factors which contribute these failures, such as : 1. inaccurate clinical diagnosis of the infections; 2 inadequate dentists knowledge on bacterial etiology; 3. inappropriate and irrrational choice of the antibiotics; 4. improper use of the antibiotics in dosage, time, interval, duration of intake etc. There are several factors to be considered in using antibiotic safely and normally, such as modus of action, bacterial sensitivity, risk of bacterial resistency, etc. In many cases we are faced to choose a combined therapy. This paper discussed the problems and methods in using antibiotics safely and rationally, as well as various indicators that have to be taken into considerations in using a combined therapy.